Pocket-size commemorative edition on the occasion of the 30th anniversary of the entry into force of the African Charter on Human and Peoples' Rights 21 October 1986 - 2016 (Pretoria University Law Press (PULP), 2016)
About the publication Marking 30 years since the entry into force of the founding document of the African human rights system - the African Charter on Human and Peoples' Rights - on 21 October 1986, the African Union designated 2016 as its "Year of Human Rights". This commemorative publication brings together six core documents that in themselves capture progressive developments of the African human rights system. In addition to the African Charter, this pocket-size publication also contains two other normative frameworks - the Protocol to the African Charter on the Rights of Women in Africa (Maputo Protocol) and the African Charter on the Rights and Welfare of the Child. The two main institutions of the system are the African Commission on Human and Peoples' Rights and the African Court on Human and Peoples' Rights. The Protocol establishing the African Court is included. In addition, the internal rules of the African Commission and the African Court are also included. Table of Contents African Charter on Human and Peoples' Rights Protocol to the African Charter on Human and Peoples' Rights on the Rights of Women in Africa African Charter on the Rights and Welfare of the Child Protocol to the African Charter on Human and Peoples' Rights on the Establishment of an African Court on Human and Peoples' Rights Rules of Procedure of the African Commission on Human and Peoples' Rights Rules of Court